2018
DOI: 10.1105/tpc.17.00380
|View full text |Cite
|
Sign up to set email alerts
|

A Role for MINIYO and QUATRE-QUART2 in the Assembly of RNA Polymerases II, IV, and V in Arabidopsis

Abstract: RNA polymerases IV and V (Pol IV and Pol V) are required for the generation of noncoding RNAs in RNA-directed DNA methylation (RdDM). Their subunit compositions resemble that of Pol II. The mechanism and accessory factors involved in their assembly remain largely unknown. In this study, we identified mutant alleles of (), (), and () that cause defects in RdDM in We found that Pol IV-dependent small interfering RNAs and Pol V-dependent transcripts were greatly reduced in the mutants. NRPE1, the largest subunit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…35 In concordance with the clustering analysis, most of these genes show specific expression in the meristematic zone. Among these genes is QQT2, which is essential for correct cell divisions during embryogenesis (32) and required for the assembly of RNA polymerases II, IV, and V (33). Additional conserved meristematic zone-enriched genes encode two nucleoporins, SAR3 and NUP43, subunits of the nuclear pore complex, which regulate nucleocytoplasmic transport of 40 protein and RNA and play important roles in hormone signaling and developmental processes (34).…”
mentioning
confidence: 99%
“…35 In concordance with the clustering analysis, most of these genes show specific expression in the meristematic zone. Among these genes is QQT2, which is essential for correct cell divisions during embryogenesis (32) and required for the assembly of RNA polymerases II, IV, and V (33). Additional conserved meristematic zone-enriched genes encode two nucleoporins, SAR3 and NUP43, subunits of the nuclear pore complex, which regulate nucleocytoplasmic transport of 40 protein and RNA and play important roles in hormone signaling and developmental processes (34).…”
mentioning
confidence: 99%
“…Previous findings revealed that IYO interacts with GPN1 and GPN2 (Muñoz et al, 2017; Li et al, 2018), two members of the GPN family of GTPases that have been linked to selective nuclear transport of Pol II (Forget et al, 2010; Carre and Shiekhattar, 2011; Staresincic et al, 2011; Minaker et al, 2013; Zeng et al, 2018). In Arabidopsis , there are three GPNs, GPN1 to GPN3.…”
Section: Resultsmentioning
confidence: 99%
“…Pol II subunits do not have NLSs, so the Pol II complex associates with the NLS-containing protein IWR1 for import into the yeast nucleus, a function that appears to be also conserved in human IWR1 (Czeko et al, 2011). Interestingly, IYO and GPN1 have been found in a Pol II subassembly complex that includes the Arabidopsis IWR1 homologue DMS4 (Li et al, 2018). It is thus plausible that the NLSs from IYO and DMS4 cooperate for import of a macro-complex formed by Pol II subunits and associated RPAP factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations